2004
DOI: 10.1159/000077803
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeting Drug Oligomycin Blocked P-Glycoprotein Activity and Triggered Apoptosis in Doxorubicin-Resistant HepG2 Cells

Abstract: Background: Mitochondria are key regulators in apoptosis. This suggests that a mitochondrion can be a target for cancer treatment. To examine the feasibility of this approach, we investigated the effect of oligomycin on the induction of apoptosis in drug-resistant cells. As a mitochondrion-targeting agent, oligomycin inhibits mitochondrial F₀F1-ATPase. Of 37,000 molecules tested against the 60 human cancer cell lines of the National Cancer Institute, oligomycin is among the top 0.1% most cell line s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
(29 reference statements)
1
33
0
1
Order By: Relevance
“…Our results showed that treating DRHEp2 with oligomycin A, an Fo-ATPase inhibitor, reduced docetaxel resistance, whereas inhibitors targeting other MRC and an MRC uncoupler did not reverse docetaxel resistance. Several lines of evidence indicate that oligomycin A is a promoter of apoptosis (Wolvetang et al, 1994;Li et al, 2004); however, other reports suggest that oligomycin A has an inhibitory effect on apoptosis (Matsuyama et al, 1998;Santamaria et al, 2006). Our results indicate that oligomycin A promotes docetaxel-induced cell death in DRHEp2 and that docetaxel resistance is linked with Fo-ATPase activity level.…”
Section: Discussionmentioning
confidence: 42%
“…Our results showed that treating DRHEp2 with oligomycin A, an Fo-ATPase inhibitor, reduced docetaxel resistance, whereas inhibitors targeting other MRC and an MRC uncoupler did not reverse docetaxel resistance. Several lines of evidence indicate that oligomycin A is a promoter of apoptosis (Wolvetang et al, 1994;Li et al, 2004); however, other reports suggest that oligomycin A has an inhibitory effect on apoptosis (Matsuyama et al, 1998;Santamaria et al, 2006). Our results indicate that oligomycin A promotes docetaxel-induced cell death in DRHEp2 and that docetaxel resistance is linked with Fo-ATPase activity level.…”
Section: Discussionmentioning
confidence: 42%
“…Oligomycin has been shown to induce apoptosis, but the mechanism of the induction has not been fully elucidated (27). We found that oligomycin enhanced the cytotoxic effect of 425.3PE by affecting the ATP pool and thereby promoting cell death.…”
Section: Discussionmentioning
confidence: 77%
“…1 These effects of 1 are of particular importance for the interference with ATP-dependent outward transport and the reversal of drug-resistant phenotypes in bacterial and mammalian cells. 2,3 Furthermore, growing interest in the mechanisms of energy disbalance in disease, to the most part (but not limited to) of cancer, opened the way to the application of 1 as a potent cytotoxic agent. Design of new compounds based on 1 scaffold is of interest, as F 0 F 1 ATP synthase inhibitors are drug candidates for the treatment of bacterial infections and cancer.…”
Section: Introductionmentioning
confidence: 99%